The Effects of an Education-Leave Program on Educational Attainment and Labor-Market Outcomes - Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2018)
I study the effect of an education leave subsidy for the employed on labor-market outcomes and educational attainment using Finnish administrative linked employer-employee panel data and matching methods. The adult education allowance is available to employees with at least eight years of work experience and allows them to take a leave for 2–18 months to participate in an education program while being compensated for a substantial part of their forgone earnings. I find large positive treatment effects on educational attainment and changing occupation. The treatment effects on earnings and employment are negative during the lock-in period and close to zero afterward. Treatment effects on pseudo-outcomes are small and with one exception not statistically significant, which supports the credibility of the identification strategy. Sensitivity analyses show that unobserved variables should have a fairly large effect on treatment assignment to change the results.
Keywords: I22; J24; H43; C21; M53; 330; Adult education; Education leave; Linked employer-employee data; Program evaluation